Tungsten Promoted Ni/Al2O3 as a Noble-Metal-Free Catalyst for the Conversion of 5-Hydroxymethylfurfural to 1-Hydroxy-2,5-Hexanedione - Duan, Ying; Wang, Rui; Liu, Qihang; Qin, Xuya; Li, Zuhuan (Frontiers in Chemistry, 2022)
The conversion of 5-hydroxymethylfurfural (HMF) to 1-hydroxy-2,5-hexanedione (HHD) represented a typical route for high-value utilization of biomass. However, this reaction was often catalyzed by the noble metal catalyst. In this manuscript, W promoted Ni/Al2O3 was prepared as a noble-metal-free catalyst for this transformation. The catalysts were characterized by XRD, XPS, NH3-TPD, TEM, and EDS-mapping to study the influence of the introduction of W. There was an interaction between Ni and W, and strong acid sites were introduced by the addition of W. The W promoted Ni/Al2O3 showed good selectivity to HHD when used as a catalyst for the hydrogenation of HMF in water. The influences of the content of W, temperature, H2 pressure, reaction time, and acetic acid (AcOH) were studied. NiWOx/Al2O3-0.5 (mole ratio of W:Ni = 0.5) was found to be the most suitable catalyst. The high selectivity to HHD was ascribed to the acid sites introduced by W. This was proved by the fact that the selectivity to HHD was increased a lot when AcOH was added just using Ni/Al2O3 as catalysts. 59% yield of HHD was achieved on NiWOx/Al2O3-0.5 at 393 K, 4 MPa H2 reacting for 6 h, which was comparable to the noble metal catalyst, showing the potential application in the production of HHD from HMF.